MADRASAH HEAD SUPERVISION IN IMPROVING TEACHER PROFESSIONAL COMPETENCE - Sailin, Mujibus; Rifa'i, Moh.; Hamzah, Muh.; Aisyah, Nur; Munif, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out how academic supervision helps improve teacher professionalism at MI ManbaulUlum in TanjungsariKrejengan, which includes the program, implementation, evaluation, supporting and inhibiting factors faced by the head of MadrsahIbtidaiyahManbaulUlumTanjungsariKrejengan. Through supervisory activities, madrasas can provide guidance, motivation and technical assistance to teachers with difficulties in learning activities to improve teacher professionalism. This research qualitative uses research. To collect data using observation data, interviews, and documentation, we spoke with the head of the madrasa, the deputy head of the madrasa, and the teacher. The results of this research show that the supervision of a madrasa director in developing teachers' professional competence is going as planned. The effects of improving the professional competence of teachers include; mastery of materials, essential mastering competencies, developing materials, sustainably developing professionalism by taking reflective actions, and utilizing information and communication technology.